â€˜Ä€Ê¼isha Bint al-ShÄá¹iâ€™s Thoughts on TarÄduf and Their Implications for the IstinbÄá¹ of Law - Imran, Maizul; Ismail, Ismail (Al-Risalah, 2019)
As a book containing miracles, in literature, the miracles of the Quran have been proven by Ê»Ä€Ê¼isha Bint al-ShÄá¹iÊ¼ through her theory iâ€˜jÄz lughawÄ«. She showed the importance of the correct method of interpretation of the QurÊ¼an from aspects of tarÄduf (synonym). However, despite following the rule of "there is no word that has the same meaning (tarÄduf) in the Quran" as commonly known in the theory of iÊ»jÄz al-qurâ€™Än (the inimitability of the QurÊ¼Än), her thoughts on tarÄduf and their implications for the istinbÄá¹ (inference) of Islamic law are still unclear. Hence, this article discusses the relation and influence of Ê»Ä€Ê¼isha Bint al-ShÄá¹iÊ¼s thoughts related to verses of laws. By studying the book of al-Iâ€™jÄz al-BayÄnÄ« lil Qur`Än wa MasÄâ€™il Ibn al-Azraq and other relevance sources, this article concludes that Ê»Ä€Ê¼isha Bint al-ShÄá¹iÊ¼s thoughts related to verses of law are still abstract and difficult to be applied, hence it does not give a significant influence on the strengthening of Islamic legal propositions.